Exercise-induced asthma: un update - Saranz, Ricardo José (2004)
Exercise-induced asthma (E.I.A) affects 12-16% of the general population and most of the patients affected by extrinsic or intrinsic asthma. Surprisingly, also a high percentage of professional and Olympic athletes are affected, showing that E.I.A. does not impair physical activity, whereas endurance sports bear a higher risk than the others. The mast cell role, late asthmatic responses, diagnosis, therapy, theories and data about immunological parameters in sports are taken into consideration in this review.